BUSINESS PLAN FOR THE DEVELOPMENT OF MONTESSORI FIRST INDONESIA EDUCATIONAL INSTITUTION IN CIREBON - Insany Sabarine; Meriza Hendri (LPPM STIE Muhammadiah Bandung, 2025)
This research aims to analyze the potential and feasibility of developing Montessori First Indonesia (MFI) in Cirebon City through the Design Thinking, Entrepreneurial Process, and Timmons Model approaches, as well as to evaluate business strategies based on Porter’s Competitive Advantage theory. The study employs a descriptive–analytical method with both qualitative and quantitative approaches. Data were collected through market observation, interviews with prospective users of educational services, and financial analysis using NPV, IRR, ROI, and Payback Period indicators. The results indicate a significant market opportunity for early childhood education institutions using the Montessori method in Cirebon, reflected by the 23.6% annual growth rate of the premium education sector and the increasing public awareness of character-based and independence-oriented learning. Based on the Design Thinking findings, the primary needs of the community are schools that offer a holistic approach and a child-friendly learning environment. MFI addresses these needs through an authentic Montessori curriculum integrated with a bilingual approach and digitalized learning management system. Financial feasibility analysis demonstrates that the project is highly viable, with a positive NPV of IDR 5.47 billion, IRR of 49%, ROI of 139.16%, and a Payback Period of two years, indicating high investment efficiency and low financial risk. The SWOT analysis positions MFI in Quadrant I (aggressive strategy), highlighting key strengths such as certified human resources, modern facilities, and strong support from the upper-middle-class market segment.